Micropropagation of Rare Endemic Species Allium microdictyon Prokh. Threatened in Kazakhstani Altai - Damelya Tagimanova; Olesya Raiser; Alevtina Danilova; Ainur Turzhanova; Oxana Khapilina (Horticulturae, 2024)
Allium microdictyon Prokh. is a rare, endemic species possessing good taste qualities and listed in the Red Book of Kazakhstan; therefore, it is subject to anthropogenic impact (food gathering, grazing, logging, fires, etc.), which leads to a substantial reduction of its area. The aim of the study was to develop a protocol for microclonal propagation of A. microdictyon. Mature seeds of A. microdictyon collected from natural habitats in the Kazakhstani Altai were used as explants. Optimization of seed sterilization methods, selection of growth regulators for inducing adventitious shoot formation and microclonal propagation, and optimization of conditions for adaptation of regenerants to ex vitro conditions were carried out. Surface sterilization of seeds with 70% EtOH and 0.01% HgCl2 is optimal for obtaining sterile and viable A. microdictyon seedlings. Sterile seedlings obtained in vitro on ½ Murashige and Skoog medium supplemented with 10 mg L−1 gibberellic acid and 0.1 mg L−1 indole-3-acetic acid (IAA) were used as a source for obtaining micropropagation cultures. Induction of adventitious organogenesis of A. microdictyon was effective on media containing 0.5 mg L−1 6-benzylaminopurine (BAP) and 1.5–2 mg L−1 zeatin. On these variants, leaf conglomerates consisting of abundantly overgrown thin leaves were formed. The effect of 0.2 mg L−1 indole-3-butyric acid (IBA) on further development of organogenesis and formation of microbulbs in A. microdictyon was shown in comparison with IAA, NAA, and PAC. Regenerated A. microdictyon plants were adapted to ex vitro conditions and resumed growth after 16–20 weeks of relative dormancy. The developed micropropagation protocol can be used to preserve germplasm and propagate for subsequent restoration of A. microdictyon populations in natural habitats.